Synergistic effects of magnetic domain re-alignment and precipitation on achieving large magnetostriction in random polycrystalline Fe-Ga alloys - Ying Chen; Tianzi Yang; Junming Gou; Ruihua Qiao; Yiqun Zhang; Tianyu Ma (Materials & Design, 2025)
High-performance magnetostriction materials are highly desired for high-precision and high sensitivity magnetostrictive devices. However, the fabrication of high-performance magnetostrictive materials has relied critically on growing single crystals and subsequent domain-aligning in the past, which require not only a strict processing control on a special instrument but also a complex structure design of devices. Herein, we report the achievement of comparable magnetostriction in random-polycrystalline ferromagnet with its domain-aligned single-crystal counterpart. As exhibited in a random-polycrystalline Fe81Ga19 (at.%) alloy, by introducing coherent tetragonal nanoprecipitates within domain-aligned cubic matrix through thermal-magnetic treating, a large saturation magnetostriction 3/2λs (λ//s − λ⊥s) as high as 465 ppm has been achieved, well exceeding that for single crystals (430 ppm). The unidirectional alignment of micro-sized magnetic domains with enlarged spontaneous magnetostriction constant (induced by the coherent nanoprecipitates) favors purely 90° domain switches during subsequent magnetization process, contributing to the high-performance magnetostriction. Therefore, our work provides a simple way for fabricating high-performance magnetostrictive materials, with which the associated device design might be simplified accordingly.